16‐4: Late‐News Paper: High Color Gamut Mini‐LED Backlight Demon based on Dual‐Emissive Perovskite Quantum Dots Films. Issue 1 (25th September 2020) - Fei, Li; Honglei, Ji; Huaishu, Xu; Bai, Zelong; Liu, Ruikuo; Jing, Li; Zhong, Haizheng
Abstract : In this work, the green and red dual emissive perovskite quantum dot embedded composite films with photoluminescence quantum yield of about 85%, transmittance of about 90% and narrow band emissions were successfully fabricated and integrated with Mini‐LEDs for LCD backlight applications.